Toboali Fortress: Architectural Heritage of Islamic Sultanate Palembang Darussalam in the Historical Context South Bangka - Muhammad Safwan Jamil (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2025)
Toboali Fort is one of the important historical relics in South Bangka that is closely related to the power of the Palembang Darussalam Sultanate. The existence of this fort not only reflects the regional defense system, but also represents the social, political, and cultural values of Islam that developed in the archipelago. This study aims to analyze the historical background of the construction of Toboali Fort and identify the Islamic architectural values reflected in the form, structure, layout, and function of the building. This study uses a qualitative approach with descriptive-analytical methods.